2021
DOI: 10.1080/20964129.2021.1978330
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of farmers’ behavior toward compensation scheme for cultivated land protection in chengdu pilot area, China

Abstract: Ecological environment compensation has been increasingly applied to promote positive behavior among farmers toward protecting the quantity, quality, and ecological environment of cultivated land. Studying farmers' behavior affected by economic incentive is necessary to promote sustainable development policies for cultivated land protection. In this study, we investigated the current situation regarding economic incentive policies for cultivated land protection, which has attracted the attention of Chinese gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The carbon emissions of cropland in the Chengdu Plain reduced to 52.45% from 2006 to 2022, which was basically the same as Lu's [60] opinion. The effects of RDI, FOS, and FCR on carbon emissions from cropland are basically the same as those of Huang, Guo, and Niu [61][62][63]. The carbon emissions caused by economic development increased first and then decreased [64], and the economic development of some districts and counties changed from promoting carbon emissions to inhibiting carbon emissions, which basically corresponded with the study results of Yu [65].…”
Section: Discussionsupporting
confidence: 74%
“…The carbon emissions of cropland in the Chengdu Plain reduced to 52.45% from 2006 to 2022, which was basically the same as Lu's [60] opinion. The effects of RDI, FOS, and FCR on carbon emissions from cropland are basically the same as those of Huang, Guo, and Niu [61][62][63]. The carbon emissions caused by economic development increased first and then decreased [64], and the economic development of some districts and counties changed from promoting carbon emissions to inhibiting carbon emissions, which basically corresponded with the study results of Yu [65].…”
Section: Discussionsupporting
confidence: 74%
“…Li [29] found that farmers' awareness of policies positively influences their willingness to participate in land transfers. Niu [30] suggests that factors such as gender, education level, labor force size, land area, migration from traditional agricultural areas, average family income, and understanding of policies significantly affect farmers' behavior. Xiao [31] argues that farmers' satisfaction levels with compensation standards, funding requirements, and government supervision are significantly influenced by factors such as their education level, land area, annual agricultural income, understanding of conservation land protection funds (CLPFs), recognition of CLPF value, and perception of changes in family economic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that male and younger farmers were more likely to adopt FQPB than female and elderly farmers [7]. Moreover, farmers are more likely to exhibit FQPB in agricultural production if their education levels and annual household incomes are relatively high [8]. Nonetheless, several studies have demonstrated that farmers' gender status and educational level do not affect FQPB [9].…”
Section: Introductionmentioning
confidence: 99%